Epidermal inclusion cyst embedded in a recurrent benign fibrous histiocytoma - Mani Makhija (Wolters Kluwer Medknow Publications, 2014)
Epidermal infundibular cysts have been known to arise from implantation of epidermis in the dermis or subcutaneous tissues. The present case illustrates the theory of implantation in an epidermal inclusion cyst in a previously operated case of recurrent benign fibrous histiocytoma.